2020
DOI: 10.5603/gp.2020.0077
|View full text |Cite
|
Sign up to set email alerts
|

Challenges on the morbidly obese endometrial cancer surgery: Laparotomy or laparoscopy, lymphadenectomy or no lymphadenectomy?

Abstract: Objectives: A considerable proportion of endometrial cancer patients are morbidly obese. Management of these cases is a serious dilemma. The aim of this study was to investigate the relevance of laparoscopic route and omission of lymphadenectomy as morbidity-reducing strategies in this special population. Material and methods: Endometrial cancer patients' archival records were retrospectively reviewed and cases with body mass index ≥ 40 kg/m 2 were selected. A comparative evaluation of their characteristics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Only 15% of our patients who underwent a systematic lymphadenectomy had positive lymph nodes (lymph node metastases). This is in line with other studies, in which a mere 15-20% of patients had positive lymph nodes after lymphadenectomy [29]. Muallem [31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Only 15% of our patients who underwent a systematic lymphadenectomy had positive lymph nodes (lymph node metastases). This is in line with other studies, in which a mere 15-20% of patients had positive lymph nodes after lymphadenectomy [29]. Muallem [31].…”
Section: Discussionsupporting
confidence: 93%
“…The risk of postoperative complications is known to be highest when this approach is used. In the future, robotassisted surgery will probably permit surgeons to use the laparoscopic approach even in morbidly obese patients and thus reduce surgical complications [29,35,36]. Additionally, the sentinel node biopsy has recently become a standard procedure and is recommended by the latest ESGO guideline [37].…”
Section: Discussionmentioning
confidence: 99%
“…Only 15 % of our patients who underwent a systematic lymphadenectomy had positive lymph nodes (lymph node metastases). This is in line with other studies, in which a mere 15-20 % of patients had positive lymph nodes after lymphadenectomy [27]. Muallem [11,29].…”
Section: Discussionsupporting
confidence: 93%
“…In a study comparing patients with a BMI > 40 kg/m 2 with those with normal weight, Pavelka et al found similar results (12). This difference in surgical management could be explained by added surgical complexity and postoperative complications in the obese population (9,20,21). The surgeon may well choose to reduce the complexity of the procedure and its potential morbidities by not performing a complete lymphadenectomy thereby avoiding conversion to laparotomy.…”
Section: Discussionmentioning
confidence: 98%
“…Urunsak et al showed that the absence of lymphadenectomy had no influence on survival in their population of severely obese women (BMI >40 kg/m 2 ), irrespective of the risk of recurrence (21). Nevertheless, a meta-analysis by Kim et al showed that systematic lymphadenectomy did improve OS in women with high-risk endometrial cancer (26).…”
Section: Discussionmentioning
confidence: 99%